2014
DOI: 10.13183/jcrg.v3i2.138
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Persian Version of Global School-based Student Health Survey Adapted for Iranian School Students

Abstract: Ab s t r a c tPurpose: Global School-based Student Health Survey (GSHS) is a project supported by the World Health Organization to assess adolescent health-risk behaviours and protective factors. The present study reports test-retest and internal consistency reliability as well as Content Validity Index (CVI) for the Persian version of GSHS and Global Youth Tobacco Survey (GYTS) adapted for Iranian students. Methods:The original English GSHS, GYTS and Optional Shisha modules were translated and back-translated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Data for the present study were collected by the reliable, valid and anonymous self-administered BPersian Version of the GSHS^ (Ziaei et al 2014) BDietary behavior^module (Global School-based Student Health Survey Core Expanded Questionnaire 2009). According to the WHO's GSHS item rationales, the questions in this module measure self-reported height and weight, frequency of hunger, fruit and vegetable consumption, carbonated soft drink consumption and frequency of eating at fast food restaurants (Global School-based Student Health Survey Item Rationale 2009).…”
Section: Description Of the Survey And Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data for the present study were collected by the reliable, valid and anonymous self-administered BPersian Version of the GSHS^ (Ziaei et al 2014) BDietary behavior^module (Global School-based Student Health Survey Core Expanded Questionnaire 2009). According to the WHO's GSHS item rationales, the questions in this module measure self-reported height and weight, frequency of hunger, fruit and vegetable consumption, carbonated soft drink consumption and frequency of eating at fast food restaurants (Global School-based Student Health Survey Item Rationale 2009).…”
Section: Description Of the Survey And Data Collectionmentioning
confidence: 99%
“…The aim of the present study was to assess the prevalence and correlates of F&V intake among a representative sample of high school students in the city of Tabriz by using the reliable and valid Persian version of the Global School-based Student Health Survey (GSHS) questionnaire (Ziaei et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The construct validity and test-retest reliability of the green space assessment scale require further study evidence. Also, a previous study showed that GSHS only had moderate internal consistency and test-retest reliability (71), so further study is needed. Furthermore, the study instrument was a selfadministered questionnaire, there could be recall bias in the answers.…”
Section: Discussion Limitationsmentioning
confidence: 97%
“…A reliable, valid and anonymous, self-administered, Persian version of the GSHS PA module questionnaire was used for data collection (Ziaei et al 2014, Global School-based Student Health Survey Core Expanded Questionnaire 2009. The questions in this module measure physical activity, travel to and from school, participation in physical education classes and participation in sedentary leisure behaviour (Global School-based Student Health Survey Item Rationale 2009).…”
Section: Data Collectionmentioning
confidence: 99%
“…Therefore, the aim of the present study was to assess the prevalence of self-reported PA activity/inactivity level and sedentary behaviour and their correlates among a representative sample of high school students in the city of Tabriz, by using the reliable and valid, Persian version of the GSHS comprehensive questionnaire (Ziaei et al 2014).…”
Section: Introductionmentioning
confidence: 99%